2018
DOI: 10.9734/jocamr/2018/26858
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Phytocomponents and Hypoglycaemic Effect of Hydro-methanolic Leaf Extract of Cnidoscolus aconitifolius(Spinach Tree) in Streptozotocin Induced - Diabetic Wistar Rats

Abstract: Introduction:The potency of plants are largely due to the presence of phytochemicals contained in it; which establishes its efficacy in the treatment of health conditions like diabetes mellitus. Aim: This study is aimed at investigating the phytocomponents and hypoglycaemic effect of hydro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…According to the grouping, animals in group 1 served as the Negative Control group and only received distilled water while those in groups 2 and 3 which served as the Extract Treatment groups received 200 and 400 mg/kg BW of the HMLECA respectively. The entire administration was by oral gavage once daily for 58 days, while the dose of the extract used was based on that of Iyke et al, 22 and the toxicity (LD50) based on the findings of Adebiyi et al 6…”
Section: Experimental Animal and Designmentioning
confidence: 99%
“…According to the grouping, animals in group 1 served as the Negative Control group and only received distilled water while those in groups 2 and 3 which served as the Extract Treatment groups received 200 and 400 mg/kg BW of the HMLECA respectively. The entire administration was by oral gavage once daily for 58 days, while the dose of the extract used was based on that of Iyke et al, 22 and the toxicity (LD50) based on the findings of Adebiyi et al 6…”
Section: Experimental Animal and Designmentioning
confidence: 99%
“…Adeniran et al [ 10 ] showed that the ethanolic extracts of its roots, stems, and leaves had obvious inhibitory effects on Bacillus subtilis and Escherichia coli , and the antibacterial effects of all extracts were better than those of some common commercial antibiotics, such as tetracycline. C. aconitifolius extracts also showed the potential to lower blood sugar, protect the stomach, prevent precancerous lesions of the colon in rats, and protect the liver [ 11 , 12 , 13 , 14 ]. In addition, the addition of C. aconitifolius pellets to conventional feeds can significantly increase the nutrient content and crude protein digestibility of feeds [ 15 , 16 , 17 ], which can help to solve the world feed resource shortage problem.…”
Section: Introductionmentioning
confidence: 99%